Effects of naphthalene acetic acid (NAA) on the plant growth and sugars effects on the cut flowers Mokara chark kuan orchid (Bioscience Journal, 2017)
A study was carried out to investigate the effects of Naphthalene Acetic Acid (NAA) and sugars on the plants and flowers quality of Mokara Chark Kuan orchid respectively. Parameters were monitored between November 2014 to March 2015, with the application of three concentrations of NAA at 25, 50 and 100 mg/L in the field. The application of 25 mg/L NAA significantly increases the plant height, number of roots and total soluble solid content of Mokara Chark Kuan orchid plants. But, there was no significant effect on the leaves number, chlorophyll content and number of flowers. In case of storage experiment, the cut Mokara Chark Kuan flowers were treated with 3 % and 6 % glucose and sucrose. Physiological parameters: fresh weight, water uptake, petal thickness, discoloration and vase life were evaluated. It can be concluded that spraying with 25 mg/L NAA enhanced the plant growth and development of Mokara Chark Kuan orchid. The study also showed that 6 % sucrose was the best treatment for maintaining the post-harvest quality as well as vase life of cut Mokara Chark Kuan orchid flowers.